Double War: Shaun Gladwell, visual culture and the wars in Afghanistan and Iraq - Messham-Muir, Christian (2015)
This book focuses on art and war and, in particular, the photographs of Shaun Gladwell, an internationally acclaimed young Australian artist who has represented Australia at a Venice Biennale and has also served as an official War Artist in Iraq and Afghanistan. The book is copiously illustrated with images that relate closely to the text, which has been researched and written by Dr Kit Messham-Muir, who conducted numerous interviews with the artist. The book has been produced by the team brought together by Matt Price of Anomie Publishing, based in London. Matt Price has collaborated with many major publishers, including Thames & Hudson. Matt Price has offered Thames & Hudson Australia exclusive rights to the first edition. The main settling point is the proliferation of information about current conflicts and the fear it is instilling throughout the world. Any text or images that can offer insights into this aspect of human behaviour is of considerable interest to a large number of people. (Thames&Hudson)